Overweight, obesity and perceptions about body weight among primary schoolchildren in Dar es Salaam, Tanzania - Mpembeni, Rose N.M.; Muhihi, Alfa J.; Maghembe, Mwanamkuu J.; Ngarashi, Davis; Lujani, Benjamin; Chillo, Omary; Khuboja, Sulende; Anaeli, Amani; Njelekela, Marina A. (Tanzania Journal of Health Research, 2014)
The increasing prevalence of overweight and obesity among children has become a public health concern both in developing and developed countries. Previous research studies have shown that favourable perception of one’s body weight is an important factor in weight control. This study determined prevalence of overweight and obesity and assessed perception about body weight among primary schoolchildren in Dar es Salaam, Tanzania. In this cross sectional study, nine schools were selected randomly from a list of all primary schools in Dar es Salaam. A structured questionnaire was used to collect data on socio-demographic characteristics and lifestyle information including perception about body weight. Height and weight were measured following standard procedures. Chi-square tests and multiple logistic regressions were used to determine factors which influence perceptions about body weight. A total of 446 children were included into the study. The mean body mass index (BMI) was 16.6±4.0kg/m2 (16.1±4.0 for males and 17.0±4.0 for females). Prevalence of overweight and obesity was 9.8% and 5.2%, respectively. The prevalence of overweight and obesity was significantly higher among girls, 13.1% and 6.3% compared to boys with 6.3% and 3.8% overweight and obese respectively (P=0.0314). Overall, the prevalence of overweight and obesity was 15.0% (10.1% among boys and 19.4% among girls). One-third (33.3%) of the children perceived their body weight as overweight or obese. Among overweight and obese children, 35.4% had unfavourable perception of their body weights. There was a statistically significant difference between perceived body weight and actual body weight as indicated by BMI for both boys and girls (P<0.05). Age of the child (AOR=O.55 95%CI 0.36-0.85) and area of residence (COR=0.64 95% CI 0.44-0.95) were found to be significant predictors of favourable perception of one’s body weight. In conclusion, the prevalence of overweight and obesity is not very high in this population. However over a third of overweight and obese children, had unfavourable perception of their body weights. We recommend targeted educational programmes about overweight and obesity and the associated health effects in order to instill a behavior of self consciousness on overweight and obesity among children in Tanzania.